Bloom! : a little book about finding love - Van Lieshout, Maria (New York : Feiwel and Friends, 2008)
Bloom, a pig who prefers flowers to mud puddles, falls in love with a "flying flower," but when the butterfly leaves she is brokenhearted until a friend gives her a reason to smile again.
Keywords: Pigs -- Fiction; Butterflies -- Fiction; Love -- Fiction; Friendship -- Fiction